THE MEDIATION EFFECT OF FINANCIAL DISTRESS ON THE RELATIONSHIP BETWEEN ESG PRACTICES TO FINANCIAL STATEMENT FRAUD (Study on Manufacturing Firm Listed in IDX between 2022 - 2023) - Virzelia Ninetta Sujarto; Anis Chariri (Diponegoro Journal of Accounting, 2025)
This study explores the influence of Environmental, Social, and Governance (ESG) practices and financial distress on the recurrence for financial statement fraud among manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2021 and 2022. From an accounting perspective, this research aims to provide insights into how a firm's sustainability practices and financial health jointly impact corporate misconduct. The analysis included 21 manufacturing firms, utilizing ESG practices to measure sustainability, the Altman Z-score as a proxy for financial distress, and the Dechow F-score to assess the likelihood of financial statement fraud. Through multiple regression and mediation analyses, the study examined both direct and indirect relationships among these variables.The results indicate that strong ESG practices is significantly associated with a lower risk of financial statement fraud, underscoring the importance of sustainability initiatives in fostering ethical corporate conduct. Although a negative relationship between ESG practices and financial distress was observed, it was not statistically significant. Conversely, financial distress was found to significantly increase the likelihood of fraudulent reporting, confirming its critical role as a risk factor. However, the study did not find support for financial distress mediating the relationship between ESG practices and financial statement fraud.